2007
DOI: 10.1364/ao.46.004680
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexing free-space optical signals using superimposed collinear orbital angular momentum states

Abstract: As a proof of concept, we experimentally demonstrate multiplexing of free-space optical signals in multiple channels labeled with different states of orbital angular momentum. The multiplexing process is carried out by a dynamic liquid-crystal spatial light modulator, while the phase function is calculated by an iterative algorithm. A binary amplitude computer-generated hologram serves as a demultiplexer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 0 publications
0
39
0
Order By: Relevance
“…Most of them rely on modulating the intensity, frequency, or polarization of light [1]. Since Allen et al first reported that optical vortices (OVs) with helical phase fronts actually carry orbital angular momentum (OAM) [2], the OAM of OVs has been considered as a new degree of freedom for optical encoding in FSO communication systems [3][4][5][6][7][8].Due to the nonradioactivity compared to the electromagnetic wave band used in contemporary communications and the uncertainty relationship inhered between the angle and OAM of OV beams [9], it is difficult for an eavesdropper to detect the transmitted information precisely, thus also showing the advantage in information security. In 2004, Gibson et al demonstrated information transferring with OAM encoding [3,4].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Most of them rely on modulating the intensity, frequency, or polarization of light [1]. Since Allen et al first reported that optical vortices (OVs) with helical phase fronts actually carry orbital angular momentum (OAM) [2], the OAM of OVs has been considered as a new degree of freedom for optical encoding in FSO communication systems [3][4][5][6][7][8].Due to the nonradioactivity compared to the electromagnetic wave band used in contemporary communications and the uncertainty relationship inhered between the angle and OAM of OV beams [9], it is difficult for an eavesdropper to detect the transmitted information precisely, thus also showing the advantage in information security. In 2004, Gibson et al demonstrated information transferring with OAM encoding [3,4].…”
mentioning
confidence: 99%
“…Most of them rely on modulating the intensity, frequency, or polarization of light [1]. Since Allen et al first reported that optical vortices (OVs) with helical phase fronts actually carry orbital angular momentum (OAM) [2], the OAM of OVs has been considered as a new degree of freedom for optical encoding in FSO communication systems [3][4][5][6][7][8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, the OAM quantum number could be any value ranging from −∞ to +∞. This property prospects the potential application of the OAM in the information field [2][3][4][5][6][7][8][9][10][11][12][13]. In recent years several groups built information transmission systems based on OAM [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a multi-channel laser communication link may use this orthogonal signal basis to support the simultaneous transmission of information from different users, each on a separate OAM channel. 5,6 Realizing the separation of vortices using optical devices is, nevertheless, a matter of current research, because all known methods show advantages and disadvantages. To actually distinguish an OAM state from another, the received vortex has to be analyzed with an optical device capable of canceling the phase dislocation.…”
Section: Introductionmentioning
confidence: 99%